Inaugurated Resurrection in Earliest Christianity - Hayter, Daniel W. (The Library of New Testament Studies, 2025)
Daniel W. Hayter explores the concept of 'inaugurated resurrection' within earliest Christianity; the view that believers have experienced a present resurrection with Christ, in advance of their final resurrection at his return. He argues that belief in inaugurated resurrection is already discernible in Paul's own writings, in large part due to the influence of Scripture, suggesting that the influence of Ezekiel 36-37 on Paul's understanding of the gift of the Spirit helps to explain this belief: Paul saw inaugurated resurrection as a way of speaking of receiving the Spirit. Hayter thus examines the reception of Ezekiel 36-37 in Second Temple Jewish literature, in order to situate Paul's own understanding of these chapters in the wider Jewish context, and follows with an extensive exploration of Ezekiel 36-37 in Paul's own writings. He argues that Paul understood Ezekiel's vision of the resurrection of dry bones to have been fulfilled in the present in the gift of God's Spirit to those in Christ, that Paul's understanding of Ezekiel is then brought to bear on a close exegesis of Romans 6.1-14, and that Paul's view of the Spirit in light of Ezekiel 36-37 helps to explain the strong connection between inaugurated resurrection and baptism.Hayter concludes that, far from being non-bodily, inaugurated resurrection, by baptism in one Spirit, implies incorporation into the resurrected body of Christ